Financial management assistance and strengthening oyster mushroom business management in the Kelompok Difable Desa (KDD) Rejo Mandiri Purworejo - Nur Siyami; Hesti Respatiningsih; Rizky Dewantara; Chairani Putri Permata; Yoga Wicaksana (Universitas Muhammadiyah Magelang, 2024)
This activity aims to manage finances and strengthen business management, enhance skills, and promote independence for people with disabilities through inclusive mentoring with partners. The method used in this activity is training and mentoring. The results of this activity show an 80% increase in partners' knowledge and skills in financial management and report preparation. An increase in mushroom sales turnover by 14% per month. The addition of 2 offline marketing access points. This PMP program is expected to make a positive contribution to achieving economic independence for the disabled group.